Effectiveness of a novel, non-intrusive, continuous-use air decontamination technology to reduce microbial contamination in clinical settings: a multi-centric study. (May 2022) - Nagaraj, S.; Chandrasingh, S.; Jose, S.; Sofia, B.; Sampath, S.; Krishna, B.; Menon, I.; Kundu, D.; Parekh, S.; Madival, D.; Nandi, V.; Ghatak, A.
Summary: Background: Despite rigorous disinfection and fumigation, healthcare-associated infection (HAI) remains a significant concern in healthcare settings. We have developed a novel airborne-microbicidal technology 'ZeBox' which clears >99.999% of airborne microbial load under controlled laboratory conditions. Aim: To evaluate the clinical performance of ZeBox in reducing airborne and surface microbial load. Methods: The study was conducted in single-bed and multi-bed intensive care units (ICUs) of two hospitals. Airborne and surface microbial loads were sampled pre and post deployment of ZeBox at pre-determined sites. Statistical significance of the reduction was determined using the Mann–Whitney U -test. Findings: ZeBox brought statistically significant reduction of both airborne and surface bacterial and fungal load. In both hospital ICUs, airborne and surface bacterial load decreased by 90% and 75% on average respectively, providing a low bioburden zone of 10–15 feet diameter around the unit. The reduced microbial level was maintained during ZeBox's operation over several weeks. Most clinical bacterial isolates recovered from one of the hospitals were antibiotic resistant, highlighting ZeBox's ability to eliminate antimicrobial-resistant bacteria among others. Conclusion: ZeBox significantly reduces airborne and surface microbial burden in clinical settings. It thereby serves an unmet need for reducing the incidence of HAI.